Use of cutting-edge technologies: incorporation and efficiency in journalism education (Herald of Journalism, 2023)
Rapid advancements in technology have revolutionized various aspects of our lives, and journalism education is no exception. As classrooms or lecture halls embrace digital tools, academic disciplines of journalism and media practitioners have the opportunity to reimagine teaching and news reporting experiences, making them more engaging, personalized, and effective. This article aims to highlight the diverse ways in which cutting-edge technology can be leveraged to enhance educational outcomes, promote digital literacy, and equip learners, including aspiring journalists, with the skills needed to thrive in a rapidly evolving world and succeed in journalism practice. A survey of 200 students from two universities in Kazakhstan revealed that the majority were satisfied with the integration of high technologies in the education system. However, challenges such as technical issues, inadequate training, and concerns about overreliance on technology were identified. This research has scientific significance as it can inform future studies on digitalization in education. It also has practical significance for journalism institutions, helping them improve the implementation of advanced technologies by considering student feedback. In conclusion, the study contributes to the development of integration of innovative technologies in journalism education since it provides detailed information about students’ opinions, who are directly affected by the process of digitalization.
Keywords: innovative technologies, education system, journalism, pedagogy, multimedia content, information and communication technologies.